Analisis Implementasi Kebijakan Sanksi Administrasi pada Pelanggaran Kendaraan Umum yang Tidak Singgah pada Terminal Seksi Operasional Suku Dinas Perhubungan Jakarta Selatan - Surahman; Khikmatul Islah (Sanskara Akuntansi dan Keuangan, 2023)
This study aims to determine the extent of the implementation of administrative sanctions on violations of public vehicles that do not stop at the Operational Section of the South Jakarta Transportation Agency, which is reflected in the increasingly orderly public transportation at Pasar Minggu, South Jakarta terminal. Qualitative research methods use methods based on the philosophy of postposistivism, while to examine natural objects, where the researcher is the key instrument, data collection techniques are carried out by triangulation (combined). Data analysis is inductive or qualitative. The results show that the implementation which is carried out by communication with public transport drivers, utilizing resources by working with the TNI and POLRI in prosecution, giving fast dispositions to the tribal transportation offices and good organizational structures have been able to implement administrative sanctions on vehicle violations. General is going well.